Respuesta :
1 Cancel 5 on both sides.
a=-5aa=−5a
2 Subtract -5a−5a from both sides.
a+5a=0a+5a=0
3 Simplify a+5aa+5a to 6a6a.
6a=06a=0
4 Divide both sides by 66.
a=0a=0
------------------------------------------------------------------------------------------
a+5=-5a+5a+5=−5a+5
1 Let a=0a=0.
0+5=-5\times 0+50+5=−5×0+5
2 Simplify 5\times 05×0 to 00.
0+5=-0+50+5=−0+5
3 Simplify 0+50+5 to 55.
5=-0+55=−0+5
4 Simplify -0+5−0+5 to 55.
5=55=5
Simplifying
a + 5 = -5a + 5
Reorder the terms:
5 + a = -5a + 5
Reorder the terms:
5 + a = 5 + -5a
Add '-5' to each side of the equation.
5 + -5 + a = 5 + -5 + -5a
Combine like terms: 5 + -5 = 0
0 + a = 5 + -5 + -5a
a = 5 + -5 + -5a
Combine like terms: 5 + -5 = 0
a = 0 + -5a
a = -5a
Solving
a = -5a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '5a' to each side of the equation.
a + 5a = -5a + 5a
Combine like terms: a + 5a = 6a
6a = -5a + 5a
Combine like terms: -5a + 5a = 0
6a = 0
Divide each side by '6'.
a = 0
Simplifying
a = 0
a + 5 = -5a + 5
Reorder the terms:
5 + a = -5a + 5
Reorder the terms:
5 + a = 5 + -5a
Add '-5' to each side of the equation.
5 + -5 + a = 5 + -5 + -5a
Combine like terms: 5 + -5 = 0
0 + a = 5 + -5 + -5a
a = 5 + -5 + -5a
Combine like terms: 5 + -5 = 0
a = 0 + -5a
a = -5a
Solving
a = -5a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '5a' to each side of the equation.
a + 5a = -5a + 5a
Combine like terms: a + 5a = 6a
6a = -5a + 5a
Combine like terms: -5a + 5a = 0
6a = 0
Divide each side by '6'.
a = 0
Simplifying
a = 0